If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -8x = 8 + -15x Add '-8' to each side of the equation. 8 + -8 + -8x = 8 + -8 + -15x Combine like terms: 8 + -8 = 0 0 + -8x = 8 + -8 + -15x -8x = 8 + -8 + -15x Combine like terms: 8 + -8 = 0 -8x = 0 + -15x -8x = -15x Solving -8x = -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. -8x + 15x = -15x + 15x Combine like terms: -8x + 15x = 7x 7x = -15x + 15x Combine like terms: -15x + 15x = 0 7x = 0 Divide each side by '7'. x = 0 Simplifying x = 0
| 6z^4(10z^5-5)= | | 2x+7-8x=-5 | | 32+48x= | | (1/4)e•e^4x=e^5/6 | | x=log15/log3 | | r^2+9=16 | | L(1/4)e•e^4x=e^5/6 | | (4x)(2y+x)(2y-x)=180 | | -4x+3(1-x)=5x+1(1-x) | | -1-5w+2-7w= | | 10y=/5 | | (9w^3-10w^2+7)8w^4= | | y=x^2+10x+29 | | V+b=g | | 3x-8=-5x+12 | | 3x+4(1-x)=5x+2(1-x) | | 0=12w^2+17w-40 | | 3x+2(1-x)=2x+5(1-x) | | 91-c=4 | | 5i(i-6)=0 | | 4x+-3(1-x)=3x+5(1-x) | | 2x^3-6x^2-48x+1=8 | | (5+3i)(2-6i)= | | -18+2w+40-5w+8=-9 | | (5y+6)(6y+5)=0 | | 4x+2(x+2)=5(x+1) | | 2x+-3(1-x)=0x+4(1-x) | | (w)=12w^2+17w-40 | | Y+112=334 | | 2(2x+x)+2(10+5)=x+x+20+15(1+1) | | x^3+4x^2-3x=0 | | f(w)=12w^2+17w-40 |